Ionic conductivity and electrochemical properties of alginate–NN4NO3-based biopolymer electrolytes for EDLC application - Norfatihah, Mazuki; Nur Muhitul Jalilah, Rasali; Sahraoui, B.; Ahmad Salihin, Samsudin (DRPM Universitas Indonesia, 2020)
The alginate doped with various content of ammonium nitrate (NH4NO3) as solid biopolymer electrolytes (SBEs) has been carried out in this work by casting method using distilled water as solvent. The impedance studies of alginate-NH4NO3 SBEs film were determined via impedance spectroscopy. The lowest value of bulk resistance, Rb shows the maximum ionic conductivity is observed at 5.56 x 10-5 S cm-1 for sample containing with 25 wt. % NH4NO3 at ambient temperature (303K). The temperature dependence of ionic conductivity has been evaluated and confirm the present electrolytes follows Arrhenius behavior. The highest conducting sample was fabricated into electrical double layer and characterized for their electrochemical properties by using cyclic voltammetry (CV) and galvanostatic charge-discharged (GCD). The specific capacitance obtained from CV analysis shows decreasing pattern as increased the scan rate. While the value of specific capacitance calculated from GCD analysis exhibits almost persistent value up to 5000th cycles.